Correction to: Weak faults at megathrust plate boundary respond to tidal stress - Takashi Tonegawa; Toshinori Kimura; Kazuya Shiraishi; Suguru Yabe; Yoshio Fukao; Eiichiro Araki; Masataka Kinoshita; Yoshinori Sanada; Seiichi Miura; Yasuyuki Nakamura; Shuichi Kodaira (Earth, Planets and Space, 2021)
An amendment to this paper has been published and can be accessed via the original article.